METHOD OF MIXED STEGANOCOMPRESSION CODING IN POSITIONAL-POLYADIC BASIS - Barannik, Dmitriy (Science-based technologies, 2025)
The article substantiates that the achievement of relevant requirements in the process of organizing video information support and information security policy is an important aspect of achieving the effectiveness of critical infrastructure management. Here it is necessary to take into account the fact that video information resources can simultaneously have two functional purposes, namely: significant information from the point of view of key influence on the effectiveness of analysis and decision-making in CRIS and DSS; containers for hiding special information in integrated information security systems. The relevance and criticality of ensuring the confidentiality of (special) information using the stage of formation and/or transmission by onboard infocommunication systems under martial law is shown. It is shown that confidentiality in the general case can be ensured by an integrated approach. For this, cryptographic protection and steganographic transformation (STT) technologies are involved. At the same time, the relevance and significance of the use of STT is increasing. At the same time, there are the following disadvantages for modern options for the combined sequential use of steganographic and compression transformations. Hence, the existing STT methods do not meet the requirements for the following indicators: the speed of the embedded message channel hidden in the encrypted video stream; steganographic container; limiting the impact on the effectiveness of compression coding; integrity of hidden information seized on the receiving side; unmasking the fact of the presence of hidden messages built into the aircraft. Thus, the purpose of the article is to increase the efficiency of steganographic transformations in the process of transmitting a compressed (encoded) video stream by infocommunication networks for the specified properties of video services using on-board ICS. A method of mixed steganocompression coding based on a positional-polyadic basis with masking has been created. The basic characteristics of the method are: created hip-compression transformations in a mixed-masked basis; implementation of two-stage code-compression implementation of the hidden message element added to the stegan-position polyadic number.